Thrombectomy vs medical management in low NIHSS acute anterior circulation stroke. (15th December 2020) - Volny, Ondrej; Zerna, Charlotte; Tomek, Ales; Bar, Michal; Rocek, Miloslav; Padr, Radek; Cihlar, Filip; Nevsimalova, Miroslava; Jurak, Lubomir; Havlicek, Roman; Kovar, Martin; Sevcik, Petr; et al.
Abstract : Objective: To undertake an effectiveness and safety analysis of EVT in patients with LVO and NIH Stroke Scale (NIHSS) score ⩽6 using datasets of multicenter and multinational nature. Methods: We pooled patients with anterior circulation occlusion from 3 prospective international cohorts. Patients were eligible if presentation occurred within 12 hours from last known well and baseline NIHSS ⩽6. Primary outcome was modified Rankin Scale (mRS) score 0–1 at 90 days. Secondary outcomes included neurologic deterioration at 24 hours (change in NIHSS of ≥2 points), mRS 0–2 at 90 days, and 90-day all-cause mortality. We used propensity score matching to adjust for nonrandomized treatment allocation. Results: Among 236 patients who fit inclusion criteria, 139 received EVT and 97 received medical management. Compared to medical management, the EVT group was younger (65 vs 72 years; p < 0.001), had more proximal occlusions ( p < 0.001), and less frequently received concurrent IV thrombolysis (57.7% vs 71.2%; p = 0.04). After propensity score matching, clinical outcomes between the 2 groups were not significantly different. EVT patients had an 8.6% (95% confidence interval [CI] −8.8% to 26.1%) higher rate of excellent 90-day outcome, despite a 22.3% (95% CI, 3.0%–41.6%) higher risk of neurologic deterioration at 24 hours. Conclusions: EVT for LVO in patients with low NIHSS score was associated with increased risk of neurologic deterioration at 24 hours. However, both EVT and medical management resulted in similar proportions of excellent clinical outcomes at 90 days. Classification of evidence: This study provides Class III evidence that for patients with acute anterior circulation ischemic strokes and LVO with NIHSS < 6, EVT and medical management result in similar outcomes at 90 days.